2m − p compromise plans with strongly clear specified main effects and two-factor interactions. Issue 12 (18th June 2018) - Ye, Shili; Wang, Dongying; Zhang, Runchu
ABSTRACT: This article studies two-level strongly clear compromise plans. We derive some necessary conditions for the existence of four classes of two-level strongly clear compromise plans which allow the estimations of some specified main effects and two-factor interactions, with the assumption that the fourth- or higher-order effects are negligible. Also, some methods for constructing 2 m − p strongly clear compromise plans are introduced.